RESIDENTIAL ENVIRONMENT EVALUATION SYSTEM CONSIDERING ENVIRONMENTAL QUALITY AND ENVIRONMENTAL LOAD FOR SUSTAINABLE DEVELOPMENT OF RESIDENTIAL DISTRICT - X.-Y. Luo; Yanyan .; J. Ge (International Association of Lowland Technology, 2009)
Residential environment is one of the most important elements for quality of life, as well as the main support for the activities of economy, culture and society. On the other hand, the improvement of residential environment quality also has been increasing the consumption of energy and emission of pollution. In this paper, we established a systematic methodology for the evaluation of sustainable residential environment, considering both residential environmental quality (Q) and residential environmental load (L). The part of Q is constructed by safety, healthy, amenity, convenience and community of residential environment. The part of L is about the environmental impact of the lifecycle of the housing and community. We hope the results of our study can contribute to the sustainable development and improvement of urban residential environment for rapidly developing China.